The Reliability and Prognosis of In-Hospital Diagnosis of Metabolic Syndrome in the Setting of Acute Myocardial Infarction - Arnold, Suzanne V. (2013)
OBJECTIVES: To examine the reliability and prognostic importance of an in-hospital diagnosis of MetS in the setting of AMI. BACKGROUND: As the factors that comprise the metabolic syndrome (MetS) are believed to be altered in the setting of an acute myocardial infarction (AMI), the diagnosis of MetS during AMI hospitalization and its prognostic significance have not been studied. METHODS: We assessed patients within a multicenter registry for metabolic factors at baseline and 1-month post-AMI and followed them for mortality and rehospitalizations. The accuracy of an inpatient diagnosis of MetS was calculated, using a 1-month follow-up as the gold standard. Patients were categorized based on MetS diagnosis at baseline and 1 month, and the combined endpoint of death or rehospitalization over 12 months was compared between groups. RESULTS: Of 1129 patients hospitalized for AMI, diagnostic criteria for MetS were met by 69% during AMI hospitalization and 63% at 1 month. Inpatient MetS diagnosis had a sensitivity and specificity for outpatient diagnosis of 87% and 61%, respectively, and was associated with an 11 times increased odds of an outpatient diagnosis (c-index=0.74). Compared with patients without MetS during hospitalization and follow-up, patients classified as MetS during AMI but not follow-up had worse outcomes; while those classified MetS at follow-up had the worst outcomes (rates for combined endpoint: 27% vs. 37% vs. 38%; log-rank p=0.01). CONCLUSIONS: In a large cohort of AMI patients, the diagnosis of MetS is common and can be made with reasonable accuracy during AMI. It is associated with poor outcomes, regardless of whether the diagnosis is confirmed during subsequent outpatient visit, and identifies a high-risk cohort of patients that may benefit from more aggressive risk factor modification.